An Experimental Investigation of the Use of Computer-Based Graphics in Decision Making - Lucas, Henry C. (Management Science, 1981)
This paper presents the results of an experiment designed to investigate the impact of computer-based graphics on decision making. The experimental task consisted of selecting quarterly reorder quantities for an importer under condition of uncertain demand. Subjects in the experiment were participants in an executive program for middle and upper level managers. Each subject received information on the cumulative probability distribution of demand and had an opportunity to run up to eight trial simulations with past demand data using his or her order quantities. After completing the trial simulations, the subjects made quarterly ordering decisions for one year in which the quantities demanded were drawn from the demand distribution. Treatments included the use of a hard copy terminal and five different types of displays on a CRT. The results of the experiment provide limited support for the use of graphics presentation in an information system. Decision or cognitive style also appears to be an important variable influencing the performance of an individual and the reaction to an information system. The implications of the findings for the design of information systems are discussed.